Dİnİ Psİkolojİ ve İslam Psİkolojİsİ Bağlamında Dİn Psİkolojİsİnİ Yenİden Düşünmek - (:unkn) unknown (My University, 2017)
İnsanın bizzat tecrübe ettiği ve hayatının her anında etkilerini hissettiği bir olgu olan din, uzun zamandır psikolojik araştırmanın konusu olmuştur. Dini bir inanca sahip olup olmamasının birey üzerindeki etkilerini inceleyen bilim dalı olan din psikolojisinin ortaya çıkışı, psikoloji ile eş zamanlıdır. Nitekim psikolojinin kuruluşunda önemli rol oynamış olan Wundt, James, Watson, Freud ve Maslow gibi psikolog, teorisyen ve araştırmacılar, bireyin inanç dünyası ile ilgili konulara eserlerinde yer vermişlerdir. Günümüze kadar olan süreçte ise din psikolojisi alanında yapılan pek çok çalışma, kutsal bir varlığa inanmayı veya inanmamayı tercih etmenin duygu, düşünce, davranış, tutum, kişilik, kimlik gibi psikolojik yapılar üzerindeki etkisine ışık tutmuştur. Psikolojinin bir alt dalı olan din psikolojisi artık zengin bir literatüre sahiptir. Din, yeme içme alışkanlıklarından sosyal ilişkilerine, dünya görüşünden aile yapısına kadar hemen her boyutta bireyi etkileme, değiştirme ve dönüştürme potansiyeline sahip olduğu için din psikolojisini araştırma alanı da psikolojinin araştırma alanı kadar geniştir. Bugün ise artık din psikolojisi, kendi alt araştırma dallarını oluşturabilecek kadar geniş bir kapsama ulaşmıştır

As a phenomenon experienced and felt the effects of it at any moment by human being himself, religion has been a subject for psychological research. The emergence of psychology of religion which investigates the effects of belief or disbelief on human life is almost simultaneous with the emergence of psychology. The pioneers of psychology like Wundt, James, Watson, Freud, and, Maslow have included the religious beliefs of individuals in their opus. Up to now, numerous studies in the field of psychology of religion have shed light on the effects of belief or disbelief to a higher being on psychological elements like emotions, thoughts, behaviors, attitudes, personality, identity, and so on. Recently, psychology of religion, a sub-branch of psychology, has a rich literature. The research area of psychology of religion is as extensive as psychology since religion has the potential to affect, to change and to transform the individual at almost all dimensions from eating and drinking habits, social relationships to family structure and world view. Today the scope of psychology of religion is wide enough to produce its own sub-fields as cognitive psychology of religion, social psychology of religion, developmental psychology of religion.Psychology of religion has branched out via new tendencies, approaches, and, research methods. Therefore, it is a necessity to drawn the lines of the area and to review the contents of it. The aim of this article is to reveal the changings of the scope of psychology of religion throughout the history and to refer to the new tendencies under the light of recent studies. It indicates various approaches in terms of attitudes towards religion in the literature. The article also presents a model to discuss these approaches systematically including examples from both the world and Turkey
RECONSIDERING PSYCHOLOGY OF RELIGION IN THE CONTEXT OF RELIGIOUS PSYCHOLOGY AND ISLAMIC PSYCHOLOGY
Keywords: Tarih